2019
DOI: 10.1128/aem.02056-18
|View full text |Cite
|
Sign up to set email alerts
|

Butyrivibrio hungateiMB2003 Competes Effectively for Soluble Sugars Released byButyrivibrio proteoclasticusB316Tduring Growth on Xylan or Pectin

Abstract: Feeding a future global population of 9 billion people and climate change are the primary challenges facing agriculture today. Ruminant livestock are important food-producing animals, and maximizing their productivity requires an understanding of their digestive systems and the roles played by rumen microbes in plant polysaccharide degradation. Butyrivibrio species are a phylogenetically diverse group of bacteria and are commonly found in the rumen, where they are a substantial source of polysaccharide-degradi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 79 publications
3
27
0
Order By: Relevance
“…A feature of MA3014 is the presence of a chromid or secondary chromosome which is also found in other well-characterized Butyrivibrio genomes ( Kelly et al. 2010 ; Palevich, Kelly, Ganesh, et al. 2019 ).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…A feature of MA3014 is the presence of a chromid or secondary chromosome which is also found in other well-characterized Butyrivibrio genomes ( Kelly et al. 2010 ; Palevich, Kelly, Ganesh, et al. 2019 ).…”
Section: Resultsmentioning
confidence: 89%
“…Overall, the coding region comprises 89.77% of the genome, which is typical of rumen Butyrivibrio and Pseudobutyrivibrio genomes sequenced within the Hungate1000 project ( Seshadri et al. 2018 ; Palevich, Kelly, Leahy, et al. 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other side, Ruminobacter abundance was decreased by a lower level of CO (2%) in low- and medium-roughage rations but increased with a high level of CO (8%) in all rations. Fermentation of polysaccharides by rumen bacteria ( Butyrivibrio and Pseudobutyrivibrio ) produces formic, butyric, and acetate acids in the rumen ( 69 ). The present study showed a higher level of butyric acid with supplementation of CO at 4 and 6% levels in all rations, which is mainly attributed to the increased number of Butyrivibrio species.…”
Section: Discussionmentioning
confidence: 99%
“…In response to MP35, we detected a 3-fold increase in the relative abundance of Butyrivibrio , together with a 1.8-fold increase in Pseudobutyrivibrio compared to the control. Bacterial taxa like Firmicutes, Butyrivibrio , and Pseudobutyrivibrio , are important degraders of polysaccharides in the rumen and produce formate, butyrate, and acetate ( 101 ).…”
Section: Discussionmentioning
confidence: 99%